Students' Perception of Vlog as A Self-Learning Media in Speaking - Dinar Faiza; Ade Christanty Yudha Bestari; Meilina Haris Mayekti (Surakarta English and Literature Journal, 2022)
Speaking is one of the most challenging skills in learning English. Many obstacles are faced when learning to speak, such as lack of motivation, fear of making mistakes, and lack of self-confidence. These problems are often found during the teaching and learning process in the classroom. A teacher is expected to continue innovating for exciting and fun learning methods and media to increase learning interest, motivation, confidence, and creativity in speaking. It is needed not only in the classroom but also in independent learning. This study aims to discover students' perception of the learning process for their speaking skills through using vlogs as a self-learning media and the effect of using vlogs on students' motivation, confidence and creativity. The researcher took the research object of the English Language Teaching Department students in UNU Purwokerto. The data were obtained by giving a speaking project as a vlog with a specific theme. Data collection was conducted by providing questionnaires and interviews to find out students' perceptions about the effect of using vlogs for the improvement of motivation, confidence and creativity and also observing the students' vlogs to find out the learning process of speaking from the aspect of pronunciation, grammar and vocabulary. Data analysis is qualitative descriptive with theories from Dulay and Fromkin (1982). This study found that based on students' perceptions, they agreed that using vlogs improved their motivation, confidence and creativity. Meanwhile, based on the observation, it was found that there were some pronunciation errors and grammar mistakes in the students' speaking, but they showed improvement in choosing vocabulary. Some students used a variety of vocabularies that were rarely used in the class.